Hybrid CoMP Mode Selection Algorithm Based on Pure User - Jihong Zhao; Xiaoting Ding; Wei Wang; Hua Qu (Dianxin kexue)
CoMP-JP and CoMP-CB are two transmission modes for coordinated multi-point and have different gains incapacity requirements and improving the system performance. Aimed at the backhaul capacity shortage， a hybrid CoMPmode selection algorithm was proposed under the traditional transmission mode selection based on the user’s group. The algorithm selects the optimal transmission mode for individual user. It can be full use of the backhaul capacity and achieve the maximal system throughput. Simulation results show that the proposed algorithm enhanced the system performance under the limited backhaul capacity at a large extent， and with the increase of users， the higher performance gain.